An In-Depth Exploration of Artificial Intelligence in Radiology: Implications for General Practitioners in Primary Care and Enhancing Diagnostic Efficiency - Hadadi , Ali Hadi; Towhari , Sami Abdullah; Alsharar, Huda Mohammed Funtul; Alfaqir, Harbah Ghanem Muteb; Aljuhayyim, Narjes Omar Hamad; Alharbi, Waleed Mohammed Nafea; Alsharari, Khulud Madallah Duhayman; Alotaibi, Abdullah Ayidh; Alotaibi, Rakan Gzian (Journal of Ecohumanism, 2024)
Background: The increasing burden on radiologists due to rising imaging demands and complexities has led to concerns about burnout and compromised patient care. As artificial intelligence (AI) technologies evolve, they present potential solutions to enhance diagnostic accuracy and efficiency in radiology. Methods: This review examines the implications of AI in radiology, particularly for general practitioners (GPs) in primary care settings. A comprehensive literature search was conducted to identify studies that highlight the applications of AI in diagnostic imaging, patient management, and engagement, as well as the ethical considerations surrounding its implementation. Results: The findings indicate that AI applications, such as machine learning algorithms, have demonstrated superior capabilities in detecting diseases in imaging studies compared to traditional methods. AI-driven tools can aid GPs in making informed decisions, improving patient outcomes by facilitating early diagnosis and personalized treatment plans. However, challenges such as integration into existing healthcare systems, training requirements, and ethical concerns regarding accountability and algorithmic bias persist. Conclusion: The integration of AI in radiology holds a significant promise for enhancing the role of general practitioners in patient care. By leveraging AI technologies, GPs can improve diagnostic accuracy, reduce the burden on radiologists, and ultimately enhance patient safety. Continued research and collaboration are essential to address the barriers to AI adoption and to ensure ethical and effective implementation in clinical practice